POLITICAL POSTERS, MEMES, AND MOVEMENTS: GRAPHIC DESIGN IN THE ERA OF SOCIAL MEDIA - Awang Besar, Nazirul Mubin; Nazrin, Nizar; Merican, Farah Merican Isahak (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
In the era of digital communication, graphic design has emerged as a vital tool for influencing political narratives, mobilising communities, and constructing collective identities. This study aims to examine the role of political posters, memes, and infographics as persuasive instruments within social media ecosystems. The objectives are (i) to analyse the influence of visual design on political mobilisation, (ii) to investigate how memes and digital graphics shape political identity, and (iii) to evaluate the ethical concerns related to visual propaganda. A qualitative content analysis was employed, drawing on secondary data from case studies of Malaysian political campaigns such as #Undi18, #Lawan, and #BenderaPutih. Data sources included published articles, social media archives, and government reports, which were thematically coded using media semiotics and visual culture frameworks. Findings reveal that visual communication significantly enhances political branding and mobilisation, but also poses risks of oversimplification and misinformation. The study underscores the necessity of visual literacy and ethical accountability in political design.